The failure of nonviolence : from the Arab spring to pccupy - Gelderloos, Peter, 1982- (Seattle, Wa : Left Bank Books, 2013)
From the Arab Spring to the plaza occupation movement in Spain, the student movement in the UK and Occupy in the US, many new social movements have started peacefully, only to adopt a diversity of tactics as they grew in strength and collective experiences. The last ten years have revealed more clearly than ever the role of nonviolence. Propped up by the media, funded by the government, and managed by NGOs, nonviolent campaigns around the world have helped oppressive regimes change their masks, and have helped police to limit the growth of rebellious social movements ... The Failure of Nonviolence examines most of the major social upheavals since the end of the Cold War to establish what nonviolence can accomplish, and what a diverse, unruly, non-pacified movement can accomplish. Focusing especially on the Arab Spring, Occupy, and the recent social upheavals in Europe, this book discusses how movements for social change can win ground and open the spaces necessary to plant the seeds of a new world.
Includes bibliographical references (pages 304-306).
Keywords: Occupy movement; Arab Spring, 2010-.; Nonviolence; Government, Resistance to; Protest movements; Youth protest movements; Government, Resistance to; Nonviolence; Occupy movement; Protest movements; Youth protest movements